2021
DOI: 10.25273/pe.v11i1.7843
|View full text |Cite
|
Sign up to set email alerts
|

Because the sky is the limit: Interpretive phenomenological analysis of millennial elementary school teachers using digital technology in the classroom

Abstract: <div><p>The population of millennials who work as elementary school teachers is currently increasing because it replaces the previous generation who will retire. This generation grows surrounded by technology and educates technology savvy too. This study aims to explore the experience of millennial teacher related to the use of technology in learning in primary schools. Two research questions were proposed, namely: 1) How did millennial teacher experience their role as teacher for elementary school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…The findings of previous researchers generally support the results of the research found in this study, namely that effective digital competencies can be the most important part of teacher learning management. Various learning innovations contained in digital literacy such as e-learning, virtual classes, gamebased learning, interactive multimedia, computer-based learning, and others can foster student learning independence (Jannah et al, 2020;Kaloeti & Manalu, 2021).…”
Section: Description Of Teacher Learning Managementmentioning
confidence: 99%
“…The findings of previous researchers generally support the results of the research found in this study, namely that effective digital competencies can be the most important part of teacher learning management. Various learning innovations contained in digital literacy such as e-learning, virtual classes, gamebased learning, interactive multimedia, computer-based learning, and others can foster student learning independence (Jannah et al, 2020;Kaloeti & Manalu, 2021).…”
Section: Description Of Teacher Learning Managementmentioning
confidence: 99%